NEONATAL OUTCOME IN PRE-ECLAMPTIC PATIENTS - Ayaz, Attiya; Muhammad, Taj; Hussain, Shaheryar A; Habib, Sadia (Journal of Ayub Medical College Abbottabad, 2009)
Background: Pre-eclampsia (PE) is defined as hypertension (blood pressure of 140/90 mm Hg on two occasion 4-6 hour apart or single reading of diastolic blood pressure of >110 mm Hg) and proteinuria developing after 20 weeks of pregnancy up to 6 weeks post partum in previously normotensive, non-proteinuric women. The aim of this study was to determine the neonatal outcome in babies born of pre-eclamptic patients. Methods: It is a cross-sectional comparative study and was carried out in department of Obstetrics and Gynaecology unit C of Ayub Teaching Hospital, Abbottabad from 1st January 2007 to 30th June 2007. The study population included all cases presenting with pre-eclampsia after 20 weeks gestation to emergency and OPD and controls (Normal subject without pre-eclampsia). Results: A total of 73 cases of pre-eclampsia were recorded in study period and were matched for age, gestational age and parity with controls. Neonatal outcome data showed a perinatal mortality of 328 neonates per 1000 total births, major cause being still births and intrauterine death (IUD). Decreased APGAR score was present in 31 cases and 3 controls. Conclusion: Pre-eclampsia has great implication on adverse neonatal outcome. The various complications seen are low APGAR score, IUD, low birth weight, intrauterine growth restriction and increased need for admission to Neonatal Intensive Care Unit (NICU). Keywords: Pre-eclampsia, Perinatal mortality, Eclampsia, IUGR, Still Birth, NICU, APGAR score